1980
DOI: 10.1073/pnas.77.1.494
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the mycoplasmas.

Abstract: The phylogenetic relationships between the mycoplasmas and bacteria have been established from a comparative analysis of their 16S rRNA oligonucleotide citalogs. The genera Mycoplasma, Spiroplasma, and Atholeplasma arose b degenerative evolution, as a deep branch of the subline of costridial ancestry that led to Bacillus and Lactobacillus.Thermoplasma has no specific relationship to the other mycoplasmas; it belongs with the archaebacteria.Mycoplasma is the general name for a group of prokaryotes that do not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
198
0
6

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(221 citation statements)
references
References 29 publications
15
198
0
6
Order By: Relevance
“…Their genomes range in size from 680 to 1,600 kb (36). Previous analyses of 16s rRNA and 5s rRNA sequences have shown that members of the class Mollicutes are phylogenetically related to gram-positive bacteria (30,40,46,48). It has been postulated that the Mollicutes arose by degenerative evolution from clostridium-like ancestors.…”
mentioning
confidence: 99%
“…Their genomes range in size from 680 to 1,600 kb (36). Previous analyses of 16s rRNA and 5s rRNA sequences have shown that members of the class Mollicutes are phylogenetically related to gram-positive bacteria (30,40,46,48). It has been postulated that the Mollicutes arose by degenerative evolution from clostridium-like ancestors.…”
mentioning
confidence: 99%
“…According to a widely accepted theory, these bacteria originated from Gram-positive bacteria by genome reduction (29). Since Gram-positive and all other bacteria so far analyzed do not carry the lipoprotein motif in the subunit b of the F 0 F 1 -ATPase, one can assume that mycoplasmas adopted this motif during the process of genome reduction either from another lipoprotein gene of the same cell or they received it by horizontal gene transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Phytoplasmas inhabit phloem sieve cells of infected plants and are transmitted by phloem-feeding insects, mainly leafhoppers and psyllids (Weintraub & Beanland, 2006;Hogenhout et al, 2008). Phylogenetic studies of genes encoding 16S rRNA and a large set of concatenated core housekeeping proteins have suggested that existing phytoplasmas share a common ancestor and are descended from low G+C Gram-positive bacteria in the Bacillus-Clostridium group (Woese et al, 1980;Weisburg et al, 1989;Gundersen et al, 1994;Zhao et al, 2005). Although the evolutionary events that led to the origin of the first phytoplasma remain to be unveiled, a hypothesis has been put forward (Wei et al, 2008a) based on the unique architecture discovered in phytoplasmal genomes (Jomantiene & Davis, 2006;Jomantiene et al, 2007): ancient phage predations and subsequent genetic recombination events played a formative role in triggering evolution of the phytoplasma clade.…”
mentioning
confidence: 99%